Особенности специализированной подготовки студентов на основе дидактической модели в проекции цифрового образования - Абылова, Г.Ж (SCIENCE and SOCIETY, 2023)
This article discusses the importance of the task of vocational education, which is the development of the skills of con- scious and effective work of students with information and the competent use of modern technologies in any kind of educational activity. The rapid saturation of information, characteristic of modern society, requires rethinking and changing the learning processes using all possible means that indicate the degree of development of information and digital technologies that exists today.
Keywords: pedagogy; model; information; digital education